The Role of Indonesian House of Representatives in Conducting Parliamentary Diplomacy in Resolving the Myanmar Humanitarian Crisis (2017 – 2019) - Muh.Alif Ridwan; Muhammad Farid; Ilmi Dwiastuti (Global Local Interactions: Journal of International Relations, 2022)
This writing aims to analyze the role of the House of Representatives of the Republic of Indonesia (DPR RI) in the midst of the humanitarian crisis that occurred in the state of Rakhine, Myanmar. This paper will discuss how DPR RI uses the concept of parliamentary diplomacy in the humanitarian crisis that occurs and how this concept can influence the decision-making process in regards to the foreign policy of the government of the Republic of Indonesia at the national, regional, and global levels. This paper uses the paradigm of liberalism and the concept of parliamentary diplomacy. In addition, this paper uses a qualitative research method.